2011
DOI: 10.5194/acp-11-4425-2011
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the carbon content of aerosols from the burning of biomass in the Brazilian Amazon using thermal, optical and thermal-optical analysis methods

Abstract: Abstract. Aerosol samples were collected at a pasture site in the Amazon Basin as part of the project LBA-SMOCC-2002 (Large-Scale Biosphere-Atmosphere Experiment in Amazonia -Smoke Aerosols, Clouds, Rainfall and Climate: Aerosols from Biomass Burning Perturb Global and Regional Climate). Sampling was conducted during the late dry season, when the aerosol composition was dominated by biomass burning emissions, especially in the submicron fraction. A 13-stage Dekati low-pressure impactor (DLPI) was used to col… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 85 publications
(128 reference statements)
0
10
0
Order By: Relevance
“…Over half of it is volatile upon heating to 360 • C and largely water soluble (Soto-García et al, 2011). Even greater OC fractions were observed in the wet season (Gunthe et al, 2009) and both periods reveal a larger OC fraction (up to 90 %) in the Aitken size range.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Over half of it is volatile upon heating to 360 • C and largely water soluble (Soto-García et al, 2011). Even greater OC fractions were observed in the wet season (Gunthe et al, 2009) and both periods reveal a larger OC fraction (up to 90 %) in the Aitken size range.…”
Section: Discussionmentioning
confidence: 93%
“…The relative impact on boundary layer CCN in this distant region will depend upon the precursors that are available to influence growth to CCN sizes and/or what other aerosol and CCN are already present at this location (e.g., combustion aerosol). The mean FT size distribution above the inversion for higher CO has a mode diameter of about a factor of 2 smaller (about an order of magnitude less mass per particle) than observed in combustion outflow near SA using these same instruments (Moore II et al, 2003) and far smaller than sizes reported for Amazon biomass burning at the surface (Rissler et al, 2006;Soto-García et al, 2011). However, deep convection over the Amazon has been found to loft aerosol to 10 km while scavenging about 90 % of the accumulation mode before advection out over the Pacific (Andreae et al, 2001).…”
Section: Discussionmentioning
confidence: 98%
“…We run the broadband and narrowband detectors with staggered gains and combine the signals from the high-gain broadband output with the low-gain narrowband output in order to maximize the detectable BC mass (per particle) range. The band ratio, calculated from the ratio of the broadband to narrowband signals, depends on the boiling-point temperature and the spectral emissivity of the incandescent material, thus providing information to distinguish BC particles from, e.g., metal particles (Stephens et al, 2003). The calibration of the SP2 was conducted up to a mass of 70 fg BC.…”
Section: Nebulizer/sp2-setupmentioning
confidence: 99%
“…Ice cores offer a unique medium to study the variability of BC concentrations over long time periods, but analyses that require large sample volumes result in low time (or depth) resolution. Furthermore, the filter-based methods have the potential to over-or underestimate the BC mass concentration due to analytical artifacts, such as charring of organic carbon (Soto-García et al, 2011), dust interference (Wang et al, 2012) or filter efficiency (Torres et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…BC has been studied in Antarctic snow since the late 1980s and early 1990s (Chýlek et al, 1987(Chýlek et al, , 1992Warren and Clarke, 1990). These initial studies used filter-based methods, which could under-or overestimate BC concentrations due to some analytical artifacts (Soto-García et al, 2011;Torres et al, 2014;Wang et al, 2012). Studies using the SP2 started appearing more than two decades later, aiming at recent snow rBC concentrations (Casey et al, 2017;Khan et al, 2019), near-surface air (Khan et al, 2018), recent-past ice cores (couple centuries - Bisiaux et al, 2012aBisiaux et al, , 2012b and the past millennia (Arienzo et al, 2017).…”
Section: Comparison With Other Rbc Records In Antarcticamentioning
confidence: 99%